The Capability of Tc-99m MIBI Total Body Scan Compared with I-131 Total Body Scan for Detecting Recurrence and Metastasis in Differentiated Thyroid Carcinoma - Pothisoonthorn, Pichanun (Journal of The Department of Medical Services, 2021)
Background: I-131 is the main radiopharmaceutical for differentiated thyroid carcinoma. However, Tc-99m MIBI is also an alternative agent, which uses to detect recurrence or metastasis in several malignancies, including differentiated thyroid carcinoma.Objective: This study aimed to evaluate the capability of Tc-99m MIBI total body scan to detect recurrence and metastasis in patients with differentiated thyroid carcinoma at Lampang Cancer Hospital, compared to the scan with I-131.Method: A retrospective study performed in the patients with differentiated thyroid carcinoma status from database post total thyroidectomy from the other hospitals who came for I-131 treatment at Lampang Cancer Hospital from July 1st, 2012 to June 30th, 2019. The patients received the total body scan with I-131 and Tc-99m MIBI to detect recurrence and metastasis. Then, the concordance tested with the Kappa test and identified the scanning method with the receiver operating characteristic (ROC).Result: The 395 patients of differentiated thyroid carcinoma received the I-131 and Tc-99m MIBI total body scans to detect recurrence and metastasis. Tc-99m MIBI whole body scan had 77.98% sensitivity, which is higher sensitivity than the I-131 scan, which had 77.52% sensitivity. The sensitivity of the Tc-99m MIBI scan for identification of recurrence, regional node metastasis, and distant metastasis was 63.49%, 79.35%, and 90.48%, respectively. The sensitivity of I-131 scintigraphy for detecting recurrence, regional node metastasis, and distant metastasis was 65.08%, 80.43%, and 85.71%, respectively. Moreover, Tc-99m MIBI total body scan had concordance with the I-131 scan.Conclusion: Tc-99m MIBI scan can detect recurrence and metastasis higher than the scan with I-131, especially distant metastasis. This modality can be the alternative scintigraphy for follow-up after treatment.